The Importance of Lifestyle Physical Activity for Thai School Students - Arsapakdee, Kritchapol; Sriprom, Sirichai (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2024)
Lifestyle physical activity in adolescence improve the level of physical activity and movement that young individuals engage in as part of their daily routines and activities outside of structured exercise or organized sports. It encompasses the everyday activities that adolescents do, such as walking, biking, playing. Physical fitness is essential for all ages, but it is significant for adolescence and children. A fit body can lead to a healthy mind and body, so it is important to make lifestyle physical activity a regular part of your life. Adolescence who are physically fit are less likely to suffer from obesity or other chronic health conditions, and they are also more likely to have better mental health. Physically active adolescence has been shown to have better academic performance and social skills. By encouraging your adolescence to be physically active, you set them up for a healthy and happy life, as lifestyle physical activity helps to improve focus and concentration. Being physically fit and well-being can also boost self-esteem and confidence, adolescence learn to appreciate their bodies and what they can do. In addition, PA changes over several transitional periods, including during the COVID-19 pandemic. In many settings, a low level of PA among children occurs as a result of adults’ poor understanding of biological and environmental changes. By understanding the timing and period of the decline or increase in PA, the school, family, and home community can create more opportunities to incorporate PA into a child’s daily life. The Thai government and policy makers can also use the results of this study as evidence in refining their strategies and designing appropriate interventions to improve PA of Thai adolescence people and prevent or delay the onset of non-communicable diseases (NCD) of the population in the long run.